2017
DOI: 10.1002/clc.22698
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of postoperative prophylactic antibiotics in reducing permanent pacemaker infections

Abstract: Background Despite limited evidence, postoperative prophylactic antibiotics are often used in the setting of permanent pacemaker implantation or replacement. The aim of this study is to investigate the efficacy of postoperative antibiotics. Hypothesis Postoperative prophylactic antibiotics may be not clinically useful. Methods We recruited 367 consecutive patients undergoing permanent pacemaker implantation or generator replacement at a tertiary referral center. Baseline demographics, clinical characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 13 publications
0
14
0
1
Order By: Relevance
“…Still, the authors stated that infection rate was much lower than anticipated. [17] In a study carried out by Lee et al, [18] the patients treated with postoperative antibiotics were found to experience a similar rate of infection as those treated with not. A recent large multicenter study evaluating the strategies commonly used in clinical practice to reduce CIED infections found that prolonged use of antimicrobials after skin closure was not effective.…”
Section: Discussionmentioning
confidence: 92%
“…Still, the authors stated that infection rate was much lower than anticipated. [17] In a study carried out by Lee et al, [18] the patients treated with postoperative antibiotics were found to experience a similar rate of infection as those treated with not. A recent large multicenter study evaluating the strategies commonly used in clinical practice to reduce CIED infections found that prolonged use of antimicrobials after skin closure was not effective.…”
Section: Discussionmentioning
confidence: 92%
“…The efficacy of postoperative antibiotics has been studied in three studies. In a prospective, observational case‐control study, Lee et al investigated the use of postoperative antibiotic therapy in 367 patients with new pacemaker implantation or replacement. The patients with defibrillator and CRT device were excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Preincisional antimicrobial prophylaxis is a mainstay of infection prevention in procedural settings. Although available evidence and surgical site infection prevention guidelines support only the use of a single preincisional dose, 4,13,22 continuation of antibiotics for >1 day is common following electrophysiology procedures. 3 Prior studies demonstrate that prolonged post-procedural antibiotics following device placement are considered the standard of care by clinical electrophysiologists.…”
Section: Discussionmentioning
confidence: 99%